Penerapan Model Problem Based Learning (Pbl) pada Pembelajaran Menulis Teks Berita Di Kelas VII A SMPN 30 Muaro Jambi - Permadi, Gideon Putera; Kusmana, Ade; Rahmawati, Rahmawati (Universitas Batanghari Jambi, 2024)
This research aims to describe the application of the problem based learning model in writing news texts in class VII Aof Smp Negeri 30 Muaro Jambi. This type of research is descriptive, with a qualitative approach. Data collection techniquesinclude observation, interviews and documentation. The data obtained are the results of interviews with Indonesian languageteachers who teach in class VII A regarding the learning implementation process. The results of this research show that theimplementation of the problem based learning model in writing news texts in class VII A of SMP Negeri 30 Muaro Jambi iscarried out in accordance with the steps of the problem based learning model. This can be seen in the steps of problem basedlearning, namely orienting students towards problems, organizing students to learn, guiding investigations, developing andpresenting work results, analyzing and evaluating the problem solving process.